Mental toughness for runners. The complete guide - Ufer, M. (Meyer & Meyer Sport (UK) Ltd., 2019)
Mental Toughness for Runners gives the reader highly effective methods for successful mental training, including self-coaching, well-founded training psychology, and thought-provoking strategies for self-reflection. The mental training presented in this book has been proven successful by numerous coaching sessions and by endurance athletes throughout the world who have achieved significant and often dramatic achievements after improving their motivation, performance, and well-being with this mental training. In addition, the exercises are supplemented with case studies from various coaching sessions. The book also delves into the science of mental training so that the reader may understand the reasons behind certain training concepts, but always the focus remains on practicing and directly applying the methods to the runner`s training. This book will guide the reader through a personal assessment of his training so that he may develop an individually tailored mental training plan which can then be integrated into everyday sports life. Every runner who reads this book will improve his mental training and ultimately his running performance. The book presents in a unique way the experiences and the know-how of a sports psychological expert, who coaches numerous runners and other endurance athletes psychologically, who also researches psychological aspects in running, regularly reports on his work in lectures, at scientific congresses and in magazine articles and who repeatedly achieves top 10 placings in international (extreme) races. Klappentext